Nep-Endotrainer: A cost-effective home-made laparoscopic simulation tool - Laudari, Uttam; Mahat, Deepak; Pradhan, Rosi; Bhandari, Suyog; Singh, Deepak Raj (Journal of Society of Surgeons of Nepal, 2021)
Introduction: Laparoscopic surgery is an established treatment modality worldwide. Opportunities to acquire this skill using expensive simulation at workplace are not always feasible due to cost, time and accessibility constraints. Nep-Endotrainer is a cost effective homemade laparoscopic simulation tool built in Nepal. Methods: Nep-Endotrainer was built using plastic manikins easily available in market. Nine apertures were created with a drilling machine, four on each side of umbilicus and one at the epigastric region. These apertures were covered by thick piece of rubber of vehicle tire with apertures in them. Logitech® C270 HD webcam was fixed interiorly with metal screws. The base of the manikin was fixed to a wooden board with hinge joint. Five different interchangeable training modules were assembled in 10×10 cm2 size wooden boards. The LED light was fixed interiorly near the web camera. The camera USB can be easily connected with laptops, tablets and mobile phones. We used discarded hand instruments from laparoscopic centers to reduce the cost of the endotrainer. Conclusion: Nep-Endotrainer is accessible to any personal budget and can be readily constructed. It allows more frequent practice at home, outside the venue and hours of surgical departments.